Formal or Functional? Traditional or Inclusive? Bible Translations as Markers of Religious Subcultures. (20th February 2020) - Perry, Samuel L; Grubbs, Joshua B
Abstract: English Bible translations are often classified along two axes: (1) whether their translation approach pursues "formal correspondence" (prioritizing literalness) or "functional equivalence" (prioritizing meaning); and (2) whether their translation approach emphasizes "gender-traditionalism" (translating gendered language literally) or "gender-inclusivism" (minimizing unnecessarily gendered language). Leveraging insights from research on how religious subcultural capital shapes consumption patterns, we examine how indicators of conservative Protestant subcultural attachment potentially shape Christians' choices of Bible translation along these axes. Compared with Catholics and "other Christians, " Conservative Protestants are more likely to read functional equivalence translations. Biblical literalists are more likely to read gender-traditionalist translations, but curiously no more likely than others to read formal correspondence translations. The link between conservative Protestant affiliation and reading a gender-traditionalist or inclusive Bible is heavily influenced by how we classify the New International Version. Importantly, we also find Bible reading and overall religiosity are positively associated with reading functional equivalence and gender-inclusive Bibles. Thus while conservative Bible beliefs seem to incline Christians toward translations that reflect conservative subcultural priorities (gender-traditionalism), consistent Bible practice is more prevalent among Christians who read more dynamic and inclusive translations.